Roteiro de exportação para as indústrias do setor moveleiro: uma abordagem prática - Rossi, Ilário (2004)
This dissertation presents an exportation routine and its aim is to facilitate the insertion process of small and micro companies from furniture sector in the international markets. Thus, this work was developed since the needs of finding alternative strategies that would give the opportunity to come into these little enterprising men in the exportation market. In this direction, with the purpose of equating the problem dealt with, this work initially searched to take inferences for the achievement of a practical and adjusted schedule to the furniture exportation micro companies, through an exploratory research to select what already exists organized and correlated with the practical of foreign commerce, in more general level, under the administrative aspects, financials, tributaries and exportation currency exchange and from this moment on, through the deductive method. As for the used procedures technician, the bibliographical research was made and it consisted of the search of information in books, periodic publications (magazines, newspapers), laws, rules, opinions, electronic resolutions and documents that are about the subject. In the case of the exportation program properly said, intend to be an extremely important source of very important consultations because it consolidates in an only document administrative rules, tributaries, commercial, financial and exportation exchange that interact in the external commerce.